FORMULATION FOR MAKING HAND SANITIZER BASED ON DURIAN PEEL EXTRACT (DURIO ZIBETHINUS MURR) IN IMPROVING ANTIBACTERIAL ABILITY - Margaretta Olivia Br Manik; Jhon Patar Sinurat; Reh Malem br Karo; Rinaldo Berutu (JURNAL KESMAS DAN GIZI (JKG), 2023)
Maceration using ethanol solvent was chosen in extracting durian rind which was then evaporated to obtain 50 grams of durian peel extract. The results of the phytochemical screening test showed that the durian rind contains tannin compounds as evidenced by the addition of Iron (III) chloride reagent to produce a black solution. In addition, durian peel also contains terpenoid compounds which have been proven using the Lieberman Burchard reagent so that a blackish brown ring is produced in the extract. The best hand sanitizer product formulation is 75 mL of 96% ethanol, 2 mL of glycerin, 3 mL of 3% hydrogen peroxide, 10 mL of distilled water and 10 mL of a 6% concentration of durian peel extract solution. The hand sanitizer product has a liquid form, has a clear brownish color, has a distinctive durian rind aroma with a pH around 6 indicating that the hand sanitizer is suitable for use. Concentration of 6% Durian fruit peel hand sanitizer has better antibacterial ability than other concentrations with a large inhibition zone of 12.4 mm which is categorized as a strong level as an antibacterial substance.